2017
DOI: 10.18632/oncotarget.16944
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and mitophagy in the context of doxorubicin-induced cardiotoxicity

Abstract: Doxorubicin (Dox) is a cytotoxic drug widely incorporated in various chemotherapy protocols. Severe side effects such as cardiotoxicity, however, limit Dox application. Mechanisms by which Dox promotes cardiac damage and cardiomyocyte cell death have been investigated extensively, but a definitive picture has yet to emerge. Autophagy, regarded generally as a protective mechanism that maintains cell viability by recycling unwanted and damaged cellular constituents, is nevertheless subject to dysregulation havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
223
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(242 citation statements)
references
References 131 publications
(179 reference statements)
13
223
0
6
Order By: Relevance
“…mTOR can inhibit autophagy, and acts as a critical negative regulator (28,29). We found that TPI decreased mTOR phosphorylation, and thus has an antithetical role in the inhibition of autophagy initiation (23).…”
Section: Discussionmentioning
confidence: 67%
“…mTOR can inhibit autophagy, and acts as a critical negative regulator (28,29). We found that TPI decreased mTOR phosphorylation, and thus has an antithetical role in the inhibition of autophagy initiation (23).…”
Section: Discussionmentioning
confidence: 67%
“…Although mitophagy is protective in most cases (28), it becomes detrimental under certain conditions (29,30). The effect of Dox on mitophagy has been previously assessed, but neither mitophagy activity nor its functional role in Dox cardiotoxicity has been unequivocally defined (33). Dox was reported to inhibit cardiac mitophagy because of the sequestration of parkin by p53 that led to decreased mitochondrial translocation of parkin and reduced mitochondria incorporation into autophagic vacuoles (34).…”
Section: Discussionmentioning
confidence: 99%
“…It is still debatable whether and how mitophagy is involved in Dox cardiotoxicity (33). Parkin is an E3 ubiquitin ligase that ubiquitinates mitochondria to trigger their degradation by mitophagy.…”
Section: Mitophagy Contributed To Dox-induced H9c2 Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Dox cardiotoxicity is attributed to elevated oxidative stress, DNA and mitochondrial damage and deleterious changes in gene expression, culminating in the dysregulation of multiple signal transduction pathways leading to cardiac cell death (Koleini and Kardami 2017). Currently, the only FDA-approved drug to mitigate Dox-induced cardiotoxicity is dexrazoxane, which has been of restricted use due to the concern for cancer outcomes (van Dalen et al 2011).…”
Section: Introductionmentioning
confidence: 99%